2022
DOI: 10.1186/s40360-022-00554-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in arsenic biotransformation is an important metabolic basis for arsenic toxicity

Abstract: Background Arsenic metabolism enzymes can affect the toxic effects of arsenic. However, the effects of different genders on the metabolites and metabolic enzymes in liver arsenic metabolism is still unclear. This study analyzed the gender differences of various arsenic metabolites and metabolic enzymes and further explored the effects of gender differences on arsenic metabolism in liver tissues of rats. Methods Rats were treated with high/medium/lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…[24] Using an animal model, researchers linked the effect of patient gender on As metabolism to different epigenetic regulations that are distinguishable between males and females. [25] In the present study, male and female patients did not have signi cant differences in Al and As serum levels, which means that gender does not cause signi cant changes in Al and As metabolism in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 44%
“…[24] Using an animal model, researchers linked the effect of patient gender on As metabolism to different epigenetic regulations that are distinguishable between males and females. [25] In the present study, male and female patients did not have signi cant differences in Al and As serum levels, which means that gender does not cause signi cant changes in Al and As metabolism in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 44%
“…Several studies have demonstrated a better methylation capacity in women than in men, and the sex differences in the metabolic biotransformation of arsenic seem to play a part in the generally lower arsenic toxicity in females than in males. [3][4][5] Improved female methylation of As can be partially explained by estrogen-dependent upregulation of the synthesis of choline as a critical cofactor in the generation of SAME, the essential methyl donor in the oxidative methylation of iAs. 4 The lower female consumption of SAME for their reduced creatinine synthesis (Sup Tbl 3) will further add to this effect.…”
Section: Sex Differences In Renal Arsenic Excretionmentioning
confidence: 99%
“…An animal study demonstrated less pronounced decreases in SAME activity after high-dose exposure to arsenate (iAsV) or arsenite (iAsIII) compared to low-or medium-dose exposure in female vs. male rats. 5 Thus, women could dispose of more SAME as an essential cofactor for oxidative methylation of iAs. Apart from the evident advantages in methylation, females also seem to exhibit improved renal antioxidative defense mechanisms due to higher expression of protective enzymes such as eNOS, Metallothionein, Mn-SOD, or Carbon-Anhydrase (Sup Tbl 3), favoring more efficient oxidative methylation of iAs.…”
Section: Sex Differences In Renal Arsenic Excretionmentioning
confidence: 99%
“…Several studies have demonstrated a better methylation capacity in women than in men, and the sex differences in the metabolic biotransformation of arsenic seem to play a part in the generally lower arsenic toxicity in females than in males. [3][4][5] Improved female methylation of As can be partially explained by estrogen-dependent upregulation of the synthesis of choline as a critical cofactor in the generation of SAME, the essential methyl donor in the oxidative methylation of iAs. 4 The lower female consumption of SAME for their reduced creatinine synthesis (App.…”
Section: Sex Differences In Renal Arsenic Excretionmentioning
confidence: 99%
“…An animal study demonstrated less pronounced decreases in SAME activity after high-dose exposure to arsenate (iAsV) or arsenite (iAsIII) compared to low-or medium-dose exposure in female vs. male rats. 5 Thus, women could dispose of more SAME as an essential cofactor for oxidative methylation of iAs. Apart from the evident advantages in methylation, females also seem to exhibit improved renal antioxidative defense mechanisms due to higher expression of protective enzymes such as eNOS, Metallothionein, Mn-SOD, or Carbon-Anhydrase (App.…”
Section: Sex Differences In Renal Arsenic Excretionmentioning
confidence: 99%